SLIDING MODE CONTROLLED CLOSED LOOP QB-CONVERTER -TPIS FED PMSM DRIVE WITH ENHANCED RESPONSE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The primary goal of this work is to identify the most appropriate controller for a QBC-TPIS fed PMSMD used high performance drives. A drive requires fast dynamic response and accurate control for its operation.This effort deals with the design, analysis &simulation of Closed loop- Quadratic Boost (QB) Converter-TPIS (Three Phase Inverter System) fed PMSM (Permanent Magnet Synchronous Motors) with Proportional-Integral (PI) & SM (Sliding mode) controller outcomes are presented. In this work duty cycle optimization of Q-Boost Converter was done by control input of SM controller. The-consequences are related in terms of-time-domain aspects like –rise-time,-peak-time,-settling-time&- steady state error. Settling time is lowered to 2s and steady-state error in speed is also reduced to 1.98rpm in Sliding Mode (SM) control. The consequence denotes the-better outcomes of Closed- loop-Quadratic-BC-TPIS fed PMSMD with SM controller.
Keywords: Convertisseur élévateur quadratique (QBC); Système d'onduleur triphasé (TPIS); Moteur synchrone à aimant permanent (PMSM); Contrôleur proportionnel-intégral (PI) et à mode glissant (SM)